Role of Shrimp Pond Management Institutions Supporting Shrimp Productivity in the Peureulak Coast, East Aceh - Suprihadi Suprihadi; Moch Farkhan; Sinar Pagi Sektiana; Baihaqi Baihaqi; Suris Nelli; Muhammad Haris (Universitas Gadjah Mada, 2022)
Shrimp pond management institutions are the primary key in increasing shrimp productivity and as a means and infrastructure for developing ponds and coordinating all activities. This study aimed to analyze the institutional management of shrimp pond areas to support shrimp productivity in the National Priority Program on the coast of Peureulak, East Aceh, Aceh. This study uses the Interpretative Structural Modeling (ISM) method. Surveys and interviews carry out data collection methods, focus group discussions (FGD) and questionnaires. Five (5) elements are analyzed, namely program objectives, influencing community sectors, program needs, main constraints, and institutions involved in program implementation. The analysis results show that support for the cultivation environment and the community, adequate facilities and infrastructure, and business capital availability are key sub-elements of the program objectives. Meanwhile, the Central Government (Ministry of Marine Affairs and Fisheries), Provincial Marine and Fisheries Service, and Fish Farm Cultivator Group are the institutions that play the most role in increasing shrimp productivity. At the same time, the delivery of technology that cannot be implemented, the construction and layout of traditional ponds and knowledge of skills and the low attitude of pond managers is the main obstacle in the achievement of program objectives. In contrast, the community sector which is influential in supporting program objectives is transportation, fisheries and settlements.